ADP ribose polymerase inhibitors for treating non-small cell lung cancer: new additions to the pharmacotherapeutic armamentarium. (12th April 2020) - Rossi, Giovanni; Zullo, Lodovica; Cerbone, Luigi; Coco, Simona; Longo, Luca; Tagliamento, Marco; Dal Bello, Maria Giovanna; Boccardo, Simona; Alama, Angela; Genova, Carlo
ABSTRACT: Introduction: Poly (ADP-ribose) polymerase inhibitors (PARPi) are already part of the armamentarium of drugs available against ovarian and breast cancer. There is less data available on the efficacy of these drugs in the treatment of non-small cell lung cancer (NSCLC). Areas covered: The authors have analyzed the preclinical studies that justified the use of PARPi in NSCLC. They then evaluate the in vivo efficacy of the combination of these drugs with chemotherapy, radiotherapy, and immunotherapy. Expert opinion: Data from clinical trials available to date have discouraged the use of PARPi in association with chemotherapy or radiotherapy in NSCLC. The knowledge available to date opens the door to the use of PARPi in association with immunotherapy. In fact, the activity of these drugs would not be based only on direct cytotoxic action, but also on the modification of the intra-tumor microenvironment, in particular by increasing the expression of PD-L1 on tumor cells. This action might potentially enhance available treatments with a modest increase in toxicity.